2022
DOI: 10.3389/ti.2022.10802
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes After Liver Transplantation With Incidental Cholangiocarcinoma

Abstract: Cholangiocarcinoma (CCA) is currently a contraindication to liver transplantation (LT) in the United Kingdom (UK). Incidental CCA occurs rarely in some patients undergoing LT. We report on retrospective outcomes of patients with incidental CCA from six UK LT centres. Cases were identified from pathology records. Data regarding tumour characteristics and post-transplant survival were collected. CCA was classified by TNM staging and anatomical location. 95 patients who underwent LT between 1988–2020 were identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“… 74 These findings were confirmed in two other retrospective multicentre follow-up studies where comparison of incidentally found “very early” vs. advanced iCCA and pT1 vs. pT2-T4 resulted in significantly different 5-year survival rates (65% vs. 45%, p = 0.02 and 80% vs. 31%, p = 0.018). 75 , 76 In line with these observations, the recently published EASL-ILCA Clinical Practice Guidelines on the management of iCCA propose the inclusion of LT as a potential treatment option for patients with very early iCCA in cirrhotic livers. 77 …”
Section: Oncologic Indications For Lt – Current State Of Affairsmentioning
confidence: 89%
“… 74 These findings were confirmed in two other retrospective multicentre follow-up studies where comparison of incidentally found “very early” vs. advanced iCCA and pT1 vs. pT2-T4 resulted in significantly different 5-year survival rates (65% vs. 45%, p = 0.02 and 80% vs. 31%, p = 0.018). 75 , 76 In line with these observations, the recently published EASL-ILCA Clinical Practice Guidelines on the management of iCCA propose the inclusion of LT as a potential treatment option for patients with very early iCCA in cirrhotic livers. 77 …”
Section: Oncologic Indications For Lt – Current State Of Affairsmentioning
confidence: 89%
“…This suggests that the definition of “early stage” could extend up to 5 cm, with tumor differentiation being a main factor associated with recurrence. In contrast, two recent retrospective analyses on national databases in the UK ( n = 40) [28 ▪ ] and USA ( n = 66) [41 ▪ ] revealed 57% vs 36% 5 year-OS rates, respectively, highlighting limitations of previous studies based on explant pathology [28 ▪ ,41 ▪ ,42–44] (Table 2). The Toronto group is conducting a prospective study on LT in cirrhotic patients with early (≤2 cm) iCCA (NCT02878473) not amenable to resection due to poor functional reserve, which will shed more light on this controversial topic.…”
Section: Intrahepatic Cholangiocarcinomamentioning
confidence: 81%
“…ICCAs (10–20% of all CCAs) originate above the second-order bile ducts, while pCCA (50–60%) and dCCA (20–30%) are located proximally and distally to the insertion of the cystic duct, respectively. LT is an emerging option for selected cases of iCCA and pCCA [28 ▪ ].…”
Section: Cholangiocarcinomamentioning
confidence: 99%